Qualitative longitudinal study of episodic disability experiences of older women living with HIV in Ontario, Canada. Issue 4 (20th April 2018) - Solomon, Patricia; O'Brien, Kelly K; Nixon, Stephanie; Letts, Lori; Baxter, Larry; Gervais, Nicole
Abstract : Objectives: To examine the episodic disability experiences of older women living with HIV over time. Design: Qualitative longitudinal study, conducting semistructured in-depth interviews on four occasions over a 20-month time frame. Inductive thematic analyses were conducted cross-sectionally and longitudinally. Setting: Participants were recruited from HIV community organisations in Canada. Participants: 10 women aged 50 years or older living with HIV for more than 6 years. Results: Two major themes related to the episodic nature of the women's disability. Women were living with multiple and complex sources of uncertainty over time including: unpredictable health challenges, worrying about cognition, unreliable weather, fearing stigma and the effects of disclosure, maintaining housing and adequate finances, and fulfilling gendered and family roles. Women describe strategies to deal with uncertainty over time including withdrawing and limiting activities and participation and engaging in meaningful activities. Conclusions: This longitudinal study highlighted the disabling effects of HIV over time in which unpredictable fluctuations in illness and health resulted in uncertainty and worrying about the future. Environmental factors, such as stigma and weather, may put older women living with HIV at a greater risk for social isolation. Strategies to promote dealing with uncertainty and building resilience are warranted.